2016
DOI: 10.1515/hsz-2016-0178
|View full text |Cite
|
Sign up to set email alerts
|

Stability and aggregation propensity do not fully account for the association of various germline variable domain gene segments with light chain amyloidosis

Abstract: Variable domain (VL) gene segments exhibit variable tendencies to be associated with light chain amyloidosis (AL). While few of them are very frequent in AL and give rise to most of the amyloidogenic light chains compiled at the sequence databases, other are rarely found among the AL cases. To analyze to which extent these tendencies depend on folding stability and aggregation propensity of the germline VL protein, we characterized VL proteins encoded by four AL-associated germline gene segments and one not as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In addition, recent electron‐microscopy studies revealed that fibril cores can be built up according to the same diverse principles as globular protein cores, including, in the same fibril, through hydrophobic, charge, and polar interactions, as illustrated by the recent structure of the tau filament, in which all three types are observed in a single fibril fold. Still, the molecular interactions alone might not be sufficient to account for the important role of the aggregation process in the disease, because it has been shown that the role of the V L genes in amyloidosis is not only determined by the V L protein stability and aggregation propensity, but that the frequencies of destabilizing mutations and susceptibility to proteolysis equally represent determinants for amyloidogenicity . Although we show this arrangement for polymorph A here, the similar regions found in β‐strand secondary structure for polymorph B (Figure A) strongly suggest that polymorph B, for which no 13 C: 15 N mixed preparations showing a single polymorph could be obtained, also adopts a similar fold.…”
Section: Figurementioning
confidence: 60%
“…In addition, recent electron‐microscopy studies revealed that fibril cores can be built up according to the same diverse principles as globular protein cores, including, in the same fibril, through hydrophobic, charge, and polar interactions, as illustrated by the recent structure of the tau filament, in which all three types are observed in a single fibril fold. Still, the molecular interactions alone might not be sufficient to account for the important role of the aggregation process in the disease, because it has been shown that the role of the V L genes in amyloidosis is not only determined by the V L protein stability and aggregation propensity, but that the frequencies of destabilizing mutations and susceptibility to proteolysis equally represent determinants for amyloidogenicity . Although we show this arrangement for polymorph A here, the similar regions found in β‐strand secondary structure for polymorph B (Figure A) strongly suggest that polymorph B, for which no 13 C: 15 N mixed preparations showing a single polymorph could be obtained, also adopts a similar fold.…”
Section: Figurementioning
confidence: 60%
“…It has been shown that this protein efficiently forms fibrils under near physiological conditions of temperature, pH and ionic strength 17,53 . In addition, it was recently demonstrated that 6aJL2 and its point mutant 6aJL2-R25G are the proteins most prone to aggregation among a group of six rV L proteins encoded by the germ line of five V L gene segments that are associated to amyloid deposition 24 . It should be noted that 6aJL2 has the germline sequence of subgroup λ6, the family of light chains that shows the strongest association with amyloid deposition 1821,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was recently demonstrated that 6aJL2 and its point mutant 6aJL2-R25G are the proteins most prone to aggregation among a group of six rV L proteins encoded by the germ line of five V L gene segments that are associated to amyloid deposition 24 . It should be noted that 6aJL2 has the germline sequence of subgroup λ6, the family of light chains that shows the strongest association with amyloid deposition 1821,24 . Hence, sequence elements contained in the segment Ile30-Gln37 are obvious candidates for the driver of the amyloid aggregation of 6aJL2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations